Potential of Interactive Learning Objects (ILOs) as non-face-to-face learning among trainee teachers in the Philippines - Namoco, Sarah O; Rozniza Zaharudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Teaching practicum is designed to provide teaching experiences to trainee teachers for the leadership role they are expected to perform as regular teachers. During practicum, trainee teachers are often away from the immediate supervision of their teachers for consultation. It is for this reason that online Interactive Learning Object (ILO), was introduced to serve them immediate answers related to teaching practice. This mixed method study aimed to evaluate the effectiveness of the ILO in terms of the manipulability, attractiveness, clarity and comprehensibility, interactivity, applicability, and its perceived strengths and weaknesses, as perceived by 70 trainee teachers and three faculty members. The ILO was introduced to the respondents for two weeks, and data was collected afterwards using online survey and online interview. Results indicated a high level of acceptability of the ILO among the respondents. Furthermore, suggestions to improve the ILO were also voiced by the respondents. The findings implicate that ILOs have the potential to be remedial learning objects for trainee teachers that will bridge the distance between them and their supervising teachers for consultation. The use of ILOs in the delivery of e-learning and distant learning undoubtedly needs to be considered by educational institutions.